Analysis of Tax Elimination with Thin Capitalization - Elok Faiqoh Himmah (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2020)
This study aims to analyze thin capitalization which is used as a way of tax avoidance. This study uses independent variables namely multinational, managerial ownership, audit committee, while the control variables are effective tax rates, profit growth, asset returns, company size, current ratio, capital intensity, and inventory intensity. The study population consisted of all non-financial companies listed on the Indonesia Stock Exchange from 2015-2019. The sample of this research is a multinational non-financial company which means having a subsidiary outside Indonesia. The statistical method used in this study is multiple linear regression analysis. The results of this study indicate that multinationality, managerial ownership, and audit committee have no significant effect on thin capitalization. As for the control variables, return on assets and company size have a significant effect on thin capitalization.